Pendidikan Islam di Era Digital: Tantangan dan Peluang pada Abad 21 - Muhammad Fatkhul Hajri (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2023)
The purpose of compiling this work is to analyze the role of digital technology in the transformation of Islamic education, challenges and opportunities in the 21st century. This literature review research identifies relevant literature sources on Islamic education in the digital era, conducts critical analysis of the selected content, and organizes information in an organized manner. thematic. This research aims to understand challenges such as changing educational paradigms and integrating technology, as well as opportunities such as wider access to learning resources and use of digital media in Islamic education. The results of this study are expected to contribute to the development of educational strategies and policies that are adaptive to the digital era. The result of this work is that the role of digital technology in Islamic education in the 21st century requires a mature approach based on the concept of digital literacy to address challenges and enrich the experience of religious learning. Islamic education in the digital era is faced with challenges of authenticity and accessibility, but offers global opportunities and interactive learning methods by developing digital literacy, internet manners, and applying relevant theories.